2023
DOI: 10.1186/s40510-022-00452-1
|View full text |Cite
|
Sign up to set email alerts
|

IPR treatment and attachments design in clear aligner therapy and risk of open gingival embrasures in adults

Abstract: Background The incidence of open gingival embrasures (OGE) in patients after fixed appliance treatment is relatively high, while there are no detailed reports on patients after clear aligner therapy. Also, no clinical studies with large sample size have investigated whether interproximal enamel reduction (IPR) can actually avoid OGE. The purpose of this study was to determine the prevalence of OGE in adults after clear aligner therapy and to investigate the risk of OGE associated with IPR treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A triangular-shaped crown may also be related to “scalloped-thin” gingiva that experiences higher risks of deficient papilla [ 31 , 33 ]. No relationship between IPR and the incidence of OGEs was observed in a recent research [ 5 ]. Similarly, no significant difference was found on crown ratio, root angulation or the amount and distribution of IPR between the two groups in our present study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A triangular-shaped crown may also be related to “scalloped-thin” gingiva that experiences higher risks of deficient papilla [ 31 , 33 ]. No relationship between IPR and the incidence of OGEs was observed in a recent research [ 5 ]. Similarly, no significant difference was found on crown ratio, root angulation or the amount and distribution of IPR between the two groups in our present study.…”
Section: Discussionmentioning
confidence: 93%
“…Several key issues, such as cost difference between the expensive clear aligners and the relative cheap fixed appliances, patient preference for appliances, and case selection, make randomized controlled tests difficult. For example, socio-economic factors may affect the patient's motivation for dental health and periodontal treatment; in addition, orthodontists may recommend clear aligners for cases who need arch expansion and prefer IPR in treatment with aligners [ 5 , 35 ]. Therefore, multicenter randomized controlled trials are needed to explore the difference in the incidence of open gingival embrasures in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear aligners are becoming increasingly popular due to their excellent aesthetic value, although these aligners are also associated with aesthetic problems such as OGE. In our previous study, we found the incidence of OGE in non-extraction patients after clear aligner therapy was relatively high at 25.7% and 40.3%, respectively, between the maxillary and mandibular central incisors ( Zhang et al, 2023 ). The biomechanics of clear aligners differ from those associated with fixed appliances.…”
Section: Introductionmentioning
confidence: 94%
“…This phenomenon may be pre-existing in the patient prior to treatment initiation, or black triangles may emerge during the treatment, particularly following the alignment of rotated incisors [29]. In the study conducted by Zhang et al, upon comparing the occurrence of black triangles between fixed appliance and clear aligner therapies in non-extraction cases, a heightened incidence of gingival embrasure opening was observed undergoing clear aligner therapy, with rates of 25.7% for maxillary incisors and 40.3% for mandibular incisors [30]. In contrast, fixed appliances exhibited incidences ranging from 22% to 36% [31].…”
Section: Aesthetics Of Gingival Contourmentioning
confidence: 99%